Green Marketing Mix and Halal Ethics: Integrating Sustainable Management in Indonesia’s Logistics Sector - Mega Tunjung Hapsari; Azmi Fahrurrizal Amrulloh (Universitas Mercu Buana, 2026)
Objectives: This study examines how halal-certified logistics companies in Indonesia integrate sustainability principles through the green marketing mix framework. It aims to analyze the implementation of green product, green price, green place, and green promotion strategies and their implications for sustainable management within halal logistics.Methodology: A qualitative descriptive method was employed to obtain in-depth insights from PT. Yudhistira Perkasa Abadi, a halal-certified logistics service provider in Surabaya, Indonesia. Data were collected through semi-structured interviews, direct observation, and document analysis, and analyzed using the Miles, Huberman, and Saldaña interactive model.Finding: Results reveal that the company implements eco-friendly fleets, optimized routing, green warehouses, and digital documentation to reduce environmental impact while maintaining halal integrity. Value-based pricing, strategic distribution networks, and ethical promotional practices further strengthen customer trust and corporate sustainability performance.Conclusion: The integration of green management and halal assurance demonstrates that environmental stewardship and Islamic business ethics are complementary. The study proposes the green halal logistics paradigm as a sustainable model for Indonesia’s logistics sector.